Kebijakan Syariah di Akar Rumput: Menelusuri Motif Politik Terbitnya Peraturan Desa Tentang Hukuman Cambuk di Kabupaten Bulukumba - Ridho Al-Hamdi; Heriansyah Anugrah (Politea : Jurnal Politik Islam, 2020)
This article examines the political motives of the emergence of the controversial village policy, namely the Padang Muslim Village Regulation No. 05 of 2006 concerning the implementation of whip punishment in Padang Village, Gantarang District, Bulukumba Regency. The purpose of this study is to find out how the political motives of the head of the Padang Village in issuing this Islamic-based regulations. This study utilizes a qualitative method with the case study approach. In data-gathering, it employs two techniques: documentation and in-depth interview. To measure the political motives, this study adopts a threefold indicator: ideology, instrumental, and identity. The finding demonstrates that, in the ideology factor, the head of village has a dominant power in issuing this policy. He argues that this policy is based on Al-Qur’an values. Due to such belief, this policy was issued. Debatable reactions were coming from many parties. In the instrumental factor, Islamic orthodox heritage in this village has been existing and is still robust among its society. It causes society who inhabits inside accepting this regulation generally. In the identity factor, most people in this village support this people although the head of village has a dominant factor. Nonetheless, among three indicators, the ideological is the driving factor influencing the emergence of this regulation.